2004
DOI: 10.1038/nrm1436
|View full text |Cite
|
Sign up to set email alerts
|

Foot and mouth: podosomes, invadopodia and circular dorsal ruffles

Abstract: The plasma membrane of many motile cells undergoes highly regulated protrusions and invaginations that support the formation of podosomes, invadopodia and circular dorsal ruffles. Although they are similar in appearance and in their formation--which is mediated by a highly conserved actin-membrane apparatus--these transient surface membrane distortions are distinct. Their function is to help the cell as it migrates, attaches and invades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
673
5
11

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(713 citation statements)
references
References 97 publications
21
673
5
11
Order By: Relevance
“…Focal adhesion kinase-related non-kinase inhibits focal adhesion kinase tyrosine phosphorylation and breast carcinoma cell invasion through Matrigel Tumor cell invasion is facilitated via cell protrusions called invadopodia that are sites of b1 integrin clustering, actin filament assembly and protease secretion (Buccione et al, 2004). As FAK facilitates invadopodia formation by v-Src (Hauck et al, 2001;Hsia et al, 2003), we investigated the localization and activity of FAK within murine 4T1 breast carcinoma cells (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Focal adhesion kinase-related non-kinase inhibits focal adhesion kinase tyrosine phosphorylation and breast carcinoma cell invasion through Matrigel Tumor cell invasion is facilitated via cell protrusions called invadopodia that are sites of b1 integrin clustering, actin filament assembly and protease secretion (Buccione et al, 2004). As FAK facilitates invadopodia formation by v-Src (Hauck et al, 2001;Hsia et al, 2003), we investigated the localization and activity of FAK within murine 4T1 breast carcinoma cells (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Efficient cell migration requires a profound cytoskeleton re-organization and the formation protrusive structures termed lamellipodia, filopodia, invadopodia and podosomes 26 . Cytoskeletal staining with rhodamine-phalloidin showed that SMCs PCSK9 +/+ respond to PDGF-BB stimulation by acquiring an elongated morphology and by inducing lamellipodia formation ( Figure 6C).…”
Section: Effect Of Pcsk9 On Smc Migrationmentioning
confidence: 99%
“…Podosomes are typically formed in monocytic cells (monocytes, macrophages, dendritic cells and osteoclasts), endothelial cells and smooth muscle cells, whereas invadopodia are mostly found in cancer cells (Buccione et al, 2004;Linder and Kopp, 2005;Ayala et al, 2006;Gimona and Buccione, 2006;Weaver, 2006;Linder, 2007). Invadosomes in fibroblasts that have been transformed with tyrosine kinases such as Src show features of both podosomes and invadopodia, and their exact identity is currently unclear.…”
Section: Open Questions In Invadosome Biologymentioning
confidence: 99%
“…However, they are most likely to involve microtubuledependent trafficking of vesicles from the Golgi. Indeed, the Golgi is always observed in close proximity to invadopodia (Buccione et al, 2004;Ayala et al, 2006), and parts of the machinery for vesicle docking and fusion, such as the v-SNARE VAMP7 (Steffen et al, 2008) or the exocyst complex (Sakurai-Yageta et al, 2008), are required for MT1-MMP accumulation at invadopodia. In addition, MMP recruitment at invadosomes seems to involve parts of the actin cytoskeleton, most notably cortactin .…”
Section: Matrix Degradationmentioning
confidence: 99%